Arthur and the Perfect Brother - Marc Tolon Brown (New York,London Turtleback Books, 2008)
Three new chapter books feature Arthur and his friends for fans ready to read on their own. Each book features longer Arthur Adventures at a third-grade reading level and has loads of kid appeal. Arthur is in top form as he attempts to settle a huge argument, hosts the Brain for a weekend, and tries to keep Francine from taking over a class play. Arthur fans will want to read and collect all of these new chapter books!
Keywords: Fiction -- Fiction